Karanie i włoski system więziennictwa: czy konstytucyjne zasady są efektywne? (Discourse of Law and Administration, 2021)
The publication discusses the constitutional regulations concerning criminal law in Italy about punishment and execution of punishment. Attention was paid to the rehabilitation nature of the imprisonment sentence. Also discussed de facto obstacles to the detainee’s rehabilitation: prison overcrowding.
Keywords: penitentiary system in Italy; whole-life imprisonment; goal of punishments; re-socializing treatment; detainee’s rehabilitation